Characterization of ligature-induced experimental periodontitis - de Molon, Rafael Scaf [UNESP]; Park, Chan Ho; Jin, Qiming; Sugai, Jim; Cirelli, Joni Augusto [UNESP] (Wiley, 2018)
We sought to better characterize the progression of periodontal tissue breakdown in rats induced by a ligature model of experimental periodontal disease (PD). A total of 60 male Sprague–Dawley rats were evenly divided into an untreated control group and a PD group induced by ligature bilaterally around first and second maxillary molars. Animals were sacrificed at 1, 3, 5, 7, 14, and 21 days after the induction of PD. Alveolar bone loss was evaluated by histomorphometry and microcomputed tomography (μCT). The immune-inflammatory process in the periodontal tissue was assessed using descriptive histologic analysis and quantitative polymerase chain reaction (qPCR). This ligature model resulted in significant alveolar bone loss and increased inflammatory process of the periodontal tissues during the initial periods of evaluation (0–14 days). A significant increase in the gene expression of pro-inflammatory cytokines, interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α), and proteins involved in osteoclastogenesis, receptor activator of nuclear factor-k B ligand (RANKL) and osteoprotegerin (OPG) was observed in the first week of analysis. In the later periods of evaluation (14–21 days), no significant alterations were noted with regard to inflammatory processes, bone resorption, and expression of cytokine genes. The ligature-induced PD model resulted in progressive alveolar bone resorption with two different phases: Acute (0–14 days), characterized by inflammation and rapid bone resorption, and chronic (14–21 days) with no significant progression of bone loss. Furthermore, the gene expressions of IL-6, IL-1β, TNF-α, RANKL, and OPG were highly increased during the progress of PD in the early periods. Research Highlights: Ligature-induced bone resorption in rats occurred in the initial periods after disease induction The bone resorption was characterized by two distinct phases: Acute (0–14 days), with pronounced inflammation and alveolar bone loss Chronic phase (14–21 days): No further disease progression Several pro-inflammatory cytokines were increased during the progress of periodontitis.
Keywords: alveolar bone loss; bone resorption; periodontal disease; periodontitis; rats; X-ray microtomography